Hubungan Antara Keaktifan dalam Mengikuti Kegiatan Posyandu Lansia dengan Tingkat Kemandirian Lansia di Posyandu Lansia Pinilih Kelurahan Gumpang Kartasura - Nurseto, Kinasih Bayu, Vinami Yulian, Ns., M.Sc.Nursing (2016)
Approximately 65% of the elderly who have health problems, accompanied by relatives, and 35% lived alone. The daily living activities is essential to basic human needs. The independence in the elderly can be judged on the ability of the elderly in conducting the activity of daily living (ADL), thereby minimizing morbidity of the elderly. "Posyandu" aimed to care for elderly people in certain areas, but the data showed that Posyandu was not utilized properly, utilized only about 22.6%, so did the Posyandu Pinilih Gumpang Kartasura. This study aimed to investigate the relationship between the activeness by following activities of posyandu with the activities of daily living in Posyandu Pinilih Gumpang Kartasura. This research used cross-sectional design. The population was the elderly who lived in the area of Posyandu Pinilih Gumpang since 2015 amounted to 129 peoples. The simple random sampling became sampling technique in this research, 69 respondents were being samples. The analysis tool in this research by using Chi-Square (2). Results revealed that Chi-Square test results obtained 22.947, with the probability value (p) = 0,000 which means there were a significant correlation between the activeness of elderly in participating Posyandu and the activities of daily living in the Posyandu Pinilih Gumpang Kartasura.